"Our Bodies Are Not Terra Nullius": Building a Decolonial Feminist Resistance to Gendered Violence. Issue 3 (3rd July 2019) - Mack, Ashley Noel; Na'puti, Tiara R.
Abstract: Gendered violence is historically and presently a colonial tool that wields power over and against Indigenous peoples, attempting to destroy or erase their sovereignty and lives. Decolonization is necessary in movements addressing gendered violence in settler colonial nation-states. In this article, we forefront Indigenous organizing as a practice of survivance and decolonial feminist theory building. We argue that decolonial feminist critique deepens our understanding of complex iterations of gendered violence. By witnessing resistant Indigenous community responses to sexual violence, we can begin to imagine and build coalitional decolonial feminist possibilities. Witnessing, we argue, is a decolonial heuristic for engaging with resistant subjectivities at the colonial difference as embodied theory and praxis of decolonial feminism.